A network pharmacology study on the main active constituents and key pharmacological pathways of Shaoyao Gancao decoction on Osteoarthritis - Qiuyue LI; Chengzhi HOU; Ping ZHANG; Xu WEI (KeAi Communications Co., Ltd., 2021)
[Abstract]: Objective: This study identifies the active constituents and molecular mechanism of Shaoyao Gancao decoction (SGD) in the treatment of osteoarthritis (OA) and provides new ideas and targets for the prevention and treatment of OA with traditional Chinese medicine (TCM). Methods: The chemical constituent profile of SGD was identified by UHPLC-Q-TOF assay. Based on the candidate active compounds, combining LC-MS with the TCM database, putative targets of SGD drug-like chemical constituents were predicted using TCMSP. The targets of disease were obtained from the Gene database. Subsequently, the compound-target network was constructed and the core potential targets were screened out by a Cytoscape plug-in. Results: Thirty-two bioactive compounds of 87 drug-like chemical constituents of SGD were identified by UHPLC-Q-TOF: 279 genes were found to be the putative targets of these compounds. In a protein-protein interaction (PPI) network, according to the comprehensive analysis of the topological parameters, 62 key targets were found. Subsequently, 23 core genes were further screened out by the cytohubba plug-in of Cytoscape resulting from a synthesis of 11 algorithms. Functional enrichment analysis suggested that SGD exerted its pharmacological effects in OA by modulating multiple pathways. Eighteen active components, 23 key targets and eight key regulatory pathways were identified, among which, CCND1, MYC, MAPK8, INS, EGF, serpine1, and AGE-RAGE signaling pathway are new targets (non-OA genes) and new mechanisms. Conclusion: This study systematically and comprehensively studied bioactive compounds and core targets and pathways of SGD on OA by LC-MS-MS and network pharmacology. These results suggest that SGD is likely to treat OA by regulating metabolic pathways, which provides important information and direction for further research.